2022
DOI: 10.1111/srt.13225
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of microneedle radiofrequency therapy in the treatment of senile purpura: A prospective study

Abstract: Background: Radiofrequency (RF) devices have been used for skin rejuvenation and treating skin laxity. It may also be effective for senile purpura (SP) based on its action of promoting neocollagenesis with minimal epidermal damage. This study aimed to evaluate the efficacy and safety of microneedle RF for treating SP of the forearms in elderly. Material and methods:In this prospective study, 23 patients who underwent a single session of microneedle RF device (GENIUS, Lutronic Co., Korea) therapy for SP were en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…59 It has been reported that the RF treatment, induces inflammatory reactions starting from immediately after treatment, which triggers the neocollagenesis as a caused by the heat distress protein generation and dermal remodeling. [60][61][62] So, the RF is a technique that meets the demands of patients seeking minimally invasive methods to remodel adipose tissue and tighten skin. Many clinical studies show the ability of the RF therapy for aesthetic skin tightening of the face and body.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…59 It has been reported that the RF treatment, induces inflammatory reactions starting from immediately after treatment, which triggers the neocollagenesis as a caused by the heat distress protein generation and dermal remodeling. [60][61][62] So, the RF is a technique that meets the demands of patients seeking minimally invasive methods to remodel adipose tissue and tighten skin. Many clinical studies show the ability of the RF therapy for aesthetic skin tightening of the face and body.…”
Section: Discussionmentioning
confidence: 99%
“…A recent research showed that RF improves skin laxity and determines gene activation in a panel of proteins that are relevant in the extracellular matrix of dermal connective tissue 59 . It has been reported that the RF treatment, induces inflammatory reactions starting from immediately after treatment, which triggers the neocollagenesis as a caused by the heat distress protein generation and dermal remodeling 60–62 . So, the RF is a technique that meets the demands of patients seeking minimally invasive methods to remodel adipose tissue and tighten skin.…”
Section: Discussionmentioning
confidence: 99%
“…The depth of the needles can be adjusted from 0.5 to 3.5 mm [98]. The RF energy heats the skin to 65-70 • C, without thermally damaging the epidermis [97,99]. The insulated needles penetrate the epidermis with minimal heating while effectively delivering the desired energy to predetermined depths [99].…”
Section: Skin Rejuvenationmentioning
confidence: 99%
“…In non‐ablative fractional laser therapy, fragmental thermal damage is stimulated in exposed skin. Radiofrequency (RF) is rapidly EVOLVING field update 9–11 . In treatment by RF, the usage of radiofrequency electromagnetic waves makes local hyperthermia via changing electrical energy to intracellular heat with individual skin structures absorption.…”
Section: Introductionmentioning
confidence: 99%
“…Radiofrequency (RF) is rapidly EVOLVING field update. 9 , 10 , 11 In treatment by RF, the usage of radiofrequency electromagnetic waves makes local hyperthermia via changing electrical energy to intracellular heat with individual skin structures absorption. The dose of light and wavelength are regulated to change the skin‐coloring, decrease erythema, and to the photo‐rejuvenation of ageing.…”
Section: Introductionmentioning
confidence: 99%